1985
DOI: 10.1073/pnas.82.9.2970
|View full text |Cite
|
Sign up to set email alerts
|

Levels of human and rat hypothalamic growth hormone-releasing factor as determined by specific radioimmunoassay systems.

Abstract: Polyclonal antibodies to synthetic human pancreatic growth hormone-releasing factor )NH2] and rat hypothalamic growth hormone-releasing factor [rhGRF(1-43)OHJ were produced in rabbits by injecting these weak immunogens, coupled to thyroglobulin and emulsified with complete Freund's adjuvant in the presence of activated charcoal, directly into the spleen. A subsequent booster in-jection by the conventional intramuscular route resulted in high-titer antibodies, which at a 1:20,000 dilution were used to develop h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…The present data verifies an abstract that reports higher hypothalamic rGRF-IR content in adult male versus female rats, and agrees with previously reported levels of this peptide [3,6,32]. Although nonsignificant sex differences in whole hypothalamic rGRF-IR content have been reported, the magni tude of these differences (35%) compares with the present study [19], We analyzed the median eminence separately in the juve nile-development study to isolate this important nerve terminal bed.…”
Section: Discussionsupporting
confidence: 61%
“…The present data verifies an abstract that reports higher hypothalamic rGRF-IR content in adult male versus female rats, and agrees with previously reported levels of this peptide [3,6,32]. Although nonsignificant sex differences in whole hypothalamic rGRF-IR content have been reported, the magni tude of these differences (35%) compares with the present study [19], We analyzed the median eminence separately in the juve nile-development study to isolate this important nerve terminal bed.…”
Section: Discussionsupporting
confidence: 61%
“…Identification of GHRH-immunoreactive cell bodies in this nucleus was unexpected, as it has not been reported for other mammals. Consistent observations of immunoreactive perikarya and fibers in the neocortex were also surprising, as only one previous study refers to immunocytochemical localization of GHRH in rat cerebral cortex (Audhya et al, 1985). In little brown bats, Laemle and Cotter (1988a) recently reported VIPlike immunoreactivity in suprachiasmatic neurons as well as in neuronal elements in the cerebral cortex.…”
Section: Ghrh Immunoreactivitymentioning
confidence: 93%
“…Although immunohistochemical and RIA studies showed that the highest SS concentrations are found in the hypothalamus [2,3], this peptide is wide spread throughout the central [4] and peripheral [5] ner vous systems, where it has been suggested that SS may have a role as a neurotransmitter or neuromodulator, thus integrating neuroendocrine and behavioral responses [6]. Similarly, the highest GRF concentrations are located in the median eminence and arcuate nucleus [7], but detect able levels of immunoreactive GRF (IR-GRF) have also been identified in extrahypothalamic brain areas, with functions yet to be defined [8], Ultrastructural [9,10] and biochemical [11,12] evi dence strongly suggest that SS and GRF may interact within the hypothalamus to modulate hypophysial GH secretion, but their regulatory interactions have not been adequately delineated. Furthermore, because GRF and SS are both synthesized and released by extrahypothala mic neurons, a possible functional interaction related to neuromodulation may exist between these neuropeptides in the cortex.…”
mentioning
confidence: 99%